Una estirpe lepera en México: Baltasar Rodríguez de los Ríos y sus primeros descendientes - Isabel Arenas Frutos (Centre de Recherches sur les Mondes Américains, 2009)
Given the poor economic conditions of the province of Huelva at the initial stage of the Discovery and colonization of the New World, many young men were eager to cross the Atlantic sea looking for a better way of life in the new extensive territories. That was the case of the aforementioned resident of the village of Lepe who, according to the documents consulted, probably sailed towards New Spain in the middle of the 16th century. Settled in the City of Mexico, he soon turned into one of the many first traders enriched through mercantile exchanges with the Philippines. He became one of the wealthiest men of the Mexican elite with properties, land rents, etc., moreover, as money-lender, his relevant loans to the Council in the capital facilitated the entrance of his two natural sons as relevant members in the local governments of Mexico and Puebla, respectively. From then onwards, and as a result of the connection between relatives, so characteristic in those centuries, his descendants mixed with government employers, traders, and landowners of the highest social scale of the viceroyalty in New Spain, as shows his extensive family tree throughout all the colonial period shows.